Influence of adding phase change materials on the physical and mechanical properties of cement mortars - Cunha, Sandra Raquel Leite (2016)
During the last years several studies of construction materials with incorporation of encapsulated phase change material (PCM) have been published. However, the utilization of non-encapsulated PCM is one of the main gaps. The main objective of this work was the study of physical and mechanical properties of cement mortars with incorporation of non-encapsulated PCM. It was possible to conclude that the utilization of non-encapsulated phase change materials can be seen as a good and more economical solution for the energy efficiency of the buildings, without prejudice of the properties.